Language is the Key: The Canadian Language Benchmarks Model - Jezak, Monika (Politics and Public Policy, 2017)
This book is intended for broad readership. Given the dearth of comprehensive appraisals of the Canadian Benchmark system, it is meant as a basic academic reference for discussion, in the Canadian context, of language policy, linguistic integration of adult migrants, second language teacher education, and taskbased language learning. It is relevant to Canadian researchers, graduate and undergraduate students, policy-makers, and various second language training stakeholders (administrators, instructors, assessors, curriculum and teaching material designers, and others). Finally, the book is of relevance internationally as well, in an ongoing reflection in the community of researchers and political decision-makers concerned with similar products abroad, such as the Common European Framework of Reference (CEFR) and the ACTFL guidelines.